Presença de anáforas em textos produzidos por aluno do nono ano de uma escola pública do Paraná: uma amostra de progressão textual - Paludo, Elizete Inês (2014)
This study aimed to verify the process of referral of the constitution written productions promoted by ninth graders of elementary education at a public school in Paraná. As proposed in ART and DAT projects, we observed the occurrence of anaphora present in the texts produced by following the scientific article and the theme "World Water Day". The initial hypothesis was established that the anaphora give evidence of the real intentions of the author to produce the information and make it public. It was considered that, if well exploited, the referrers elements reveal themselves allies in the development of linguistic competence of the student. Based on studies of Textual Linguistics, was based on works of researchers based on socio-cognitive and interactionist perspective of language, the language they consider a form of cognition socio-historical and highly interactive nature. Is focused as the process resumed occurred and what were the strategies most used in textual progression. Two texts were selected to compose the corpus, because they are representative of the most prevalent forms of identification. In order to make the didactic transposition so that they can apply these concepts to elementary education, attention reassembled the text as unit of analysis. To take account of the investigative process, this work was organized around three issues: language, text and anaphora. From the verification of how the student dealt with the resume in their written productions, judgmental and argumentative proposals were investigated. As a result, the study showed that, to have dominion over the handling of linguistic elements in the text, students need to enhance their capacity readers